2009
DOI: 10.2169/internalmedicine.48.1829
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome and Prolactinoma Association

Abstract: Hyperprolactinemia is the most common pituitary hormone hypersecretion syndrome in both men and women. Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathies affecting 5%-10% of reproductive age women. Here, we present a patient with irregular menses, obesity, hirsutism and infertility, and hyperprolactinemia who was diagnosed as PCOS and prolactinoma and admitted to our clinic. Prolactinoma and PCOS association is a rare condition. This 33-year-old woman was admitted to the internal medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
8
1
1
Order By: Relevance
“…On the other hand, polycystic ovarian morphologly may be seen in 20% of women in the reproductive age group and 5% of them have PCOS (25). In the literature, a few studies and case reports indicates a close association between PCOS and pro-lactinoma, but there is no prospective study evaluating ovarian morphology in patients with prolactinoma (26,27). In the present study, an increased prevalence of PCO in patients was seen with prolactinoma.…”
Section: Discussioncontrasting
confidence: 37%
“…On the other hand, polycystic ovarian morphologly may be seen in 20% of women in the reproductive age group and 5% of them have PCOS (25). In the literature, a few studies and case reports indicates a close association between PCOS and pro-lactinoma, but there is no prospective study evaluating ovarian morphology in patients with prolactinoma (26,27). In the present study, an increased prevalence of PCO in patients was seen with prolactinoma.…”
Section: Discussioncontrasting
confidence: 37%
“…Several authors have reported the normalization of prolactin secretion and shrinkage or disappearance of macro- or microprolactinomas in patients treated with bromocriptine or cabergoline, with recovery of fertility (17, 36, 37). In our study, long-term bromocriptine treatment between 2 and 6 months of age succeeded in the control of obesity, pituitary growth and disturbances in the hormone profile of hCGβ+ females (fertility was not tested).…”
Section: Discussionmentioning
confidence: 99%
“…10,17 In addition, as there is no clear cut-off value of serum PRL level that could be used to distinguish between functional hyperprolactinaemia and the presence of a prolactinoma in PCOS, the criteria for further evaluation of such patients with pituitary imaging rely largely upon each clinician's threshold. 10,17 In addition, as there is no clear cut-off value of serum PRL level that could be used to distinguish between functional hyperprolactinaemia and the presence of a prolactinoma in PCOS, the criteria for further evaluation of such patients with pituitary imaging rely largely upon each clinician's threshold.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently a paucity of data on the association between PCOS and prolactinomas. 10,17 In addition, as there is no clear cut-off value of serum PRL level that could be used to distinguish between functional hyperprolactinaemia and the presence of a prolactinoma in PCOS, the criteria for further evaluation of such patients with pituitary imaging rely largely upon each clinician's threshold.…”
Section: Introductionmentioning
confidence: 99%